Peran Pustakawan dalam Manajemen Informasi - Komarudin Komarudin (IAIN Ponorogo, 2010)
Information management is a concept that can be viewed differently depending on the context and application. management of information can be apllied to public or private sector, non profit organization or commercial enterprise. Similarly, in the context of library, although the main task of library which provide the access of information that contains knowledge and wisdom for its user is uncchanching, the task of managing information continnues to grow and change. the library deals with more challenging task to prepare precise information to its user at the right time and at the right moment for the right reasons and in the correct format as well. At this time the librarians and information managers in the library and information center should improve their capabilities in information management. Information management is very important. This paper discusses the concept of information, the concept of information management with several aspects in it, information managers in managing information in an effort to provide knowledge to its user.